Crabgrass as a Forage and Hay Crop - Ann Rachel Blount; D. M. Ball; Richard K. Sprenkel; Robert O. Myer; Timothy D. Hewitt (EDIS, 2003)
Crabgrass is a high quality summer annual forage grass that is well adapted to the sandy soils and climatic conditions of the southern Coastal Plain. While it is often considered to be a weedy species, it is a valuable temporary summer forage crop, particularly on open land that is planted to vegetables or row crops, and used in a rotation as pasture for livestock grazing or hay production. This document is SS-AGR-193, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published August 2003.